THE COMPLEMENTARY ROLE OF PRIVATE HEALTHCARE PROVIDERS: PERSPECTIVES OF THE REGULATOR, PROVIDER AND CARE SEEKERS IN THE UPPER WEST REGION OF GHANA - Dugle, G.; Akanbang, B. A. A.; Abiiro, G. A. (UDS International Journal of Development, 2018)
This study explored the perspectives of regulators, private healthcare providers and healthcare seekers on the complementary role of private sector providers in the Upper West Region of Ghana. A mixed method approach was adopted. Key informant interviews were conducted with regional and district directors of health services as regulators, and managers of private healthcare facilities as providers, while a semi-structured questionnaire was administered to healthcare seekers. The World Health Organisation’s framework on the three overall goals of a health system: improving health, responding to client expectation and financial fairness of care formed the basis for the collection and analysis of data. The data was collected in April, 2014. Overall, all three stakeholders acknowledged that private providers complement the services of public healthcare providers. Faith-based providers use their links with foreign partners to provide specialist expatriate services, a great relief to care seekers. Private healthcare is perceived to be responsive, both ethically and in relation to expectations of care seekers. Professionalism and quality in private facilities present them as preferred alternatives to public provision. Private care is also tailored to reflect the different social preferences of care seekers. Private provision in the Region is also perceived to be fair in terms of compliance with financial standards, costs and value for money. For instance, 96% of care seekers noted that private care gave them better value for money than public provision. The study also reveals that private healthcare provision is evolving, taking on traditional public provider roles such as vaccinations, immunisations and family planning, in order to remain a relevant partner as well as a preferred choice of care seekers. Policy makers and researchers need to employ robust approaches through which a broad range of stakeholders are engaged in evaluating the emerging complementary role of private providers in order to harness same. Keywords: Healthcare providers, Complementary healthcare, Public-private partnership, Health services management